Video Iklan Layanan Masyarakat Komisi Pemilihan Umum Kabupaten Semarang sebagai Media Sosialisasi kepada Kaum Pemilih Pemula - Tri Wahyu Prasetyo; Bayu Eko Prasetyo; Aulya Rafly Salsabil; Sherin Natasya Priscilla; Deiva Olivia Yuliana Rolos; Putri Hergianasari (Universitas Kristen Satya Wacana Salatiga, 2021)
The integrated field program carried out by the FISKOM Integrated Field Learning group at the General Election Commission of Semarang Regency is an implementation of community service. The group made direct observations to see what activities the group at the Semarang Regency General Election Commission could assist with and then chose the right program to be able to make a scientific contribution. The low participation of several community groups, one of which is the novice voters, is one of the groups' concerns in taking the activity of making Community Service Advertisements videos. Public Service Advertisement Video as a medium to provide additional insight to the public and is expected to contribute to the Semarang Regency General Election Commission to socialize to novice voters about the importance of being involved in elections and elections and avoiding not voting or money politics in the upcoming elections.